2019
DOI: 10.4081/jlimnol.2019.1855
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a Planktonic Integrity Index (PII) for Jingpo Lake, China

Abstract: A Planktonic Integrity Index (PII) for the China’s largest alpine barrier lake (Jingpo Lake) was developed to assess the water quality of Jingpo Lake by using phytoplankton and zooplankton metrics. Phytoplankton and zooplankton assemblages were sampled at 26 sites in Jingpo Lake. A total of 140 species of phytoplankton and 92 species of zooplankton were obtained in the investigations. We used a stepwise process to evaluate properties of candidate metrics and selected five for the PII: Algal cell abundance, Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Its application in water quality monitoring has attracted the attention of an increasing number of researchers [21], who currently use this method to study the composition, distribution characteristics, and factors influencing the microplankton eukaryotic community [19,22]. In the Danjiangkou Reservoir, alterations in water quality and the related structure of the phytoplanktonic eukaryote community seem particularly important for studying temporal and spatial changes in sediment nutrients, heavy metal concentrations, and phytoplanktonic, macroscopic algal, bacterial and fungal taxa [8,[23][24][25][26]. Many studies have shown that dissolved oxygen (DO), chlorophyll a (Chla), water temperature (WT), pH, and ammonia nitrogen (NH 3 -N) may be the main factors affecting planktonic eukaryotes [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Its application in water quality monitoring has attracted the attention of an increasing number of researchers [21], who currently use this method to study the composition, distribution characteristics, and factors influencing the microplankton eukaryotic community [19,22]. In the Danjiangkou Reservoir, alterations in water quality and the related structure of the phytoplanktonic eukaryote community seem particularly important for studying temporal and spatial changes in sediment nutrients, heavy metal concentrations, and phytoplanktonic, macroscopic algal, bacterial and fungal taxa [8,[23][24][25][26]. Many studies have shown that dissolved oxygen (DO), chlorophyll a (Chla), water temperature (WT), pH, and ammonia nitrogen (NH 3 -N) may be the main factors affecting planktonic eukaryotes [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the TP of Dongting Lake remained high. Local authorities urgently need practical evaluation indicators and methods that can comprehensively reflect the water quality status of Dongting Lake and other large and medium-sized river-connected lakes (e.g., Jingpo Lake [57] in northern China).…”
Section: Biological Assessment Of Water Quality Based On Diatom Indicesmentioning
confidence: 99%
“…In particular, the waterways in the east Dongting Lake area have largely the same hydrological characteristics as rivers, and the phytoplankton of Dongting Lake is dominated by diatoms (in both species and biomass) [55,69]. Previous studies have also shown that the index of biotic integrity (IBI) can suitably assess the water quality of rivers and lakes [56,57], thus providing the foundation for the biological evaluation of the water quality of Dongting Lake based on diatoms. Using the water quality and diatom data of Dongting Lake from 2017 to 2022, this study aimed to clarify: (1) the spatio-temporal succession characteristics of diatom communities, diatom indices and water quality indicators, (2) the relationship between diatom indices and water quality indicators, and (3) the feasibility of using diatom indices to replace water quality indices in water quality evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the waterways in the east Dongting Lake area have largely the same hydrological characteristics as rivers, and the phytoplankton of Dongting Lake is dominated by diatoms (in both species and biomass) (Yin et al, 2022;Wang et al, 2012). Previous studies have also shown that the index of biotic integrity (IBI) can suitably assess the water quality of rivers and lakes (Wang et al, 2015;Wang et al, 2019), thus providing the foundation for the biological evaluation of the water quality of Dongting Lake based on diatoms. Using the water quality and diatom data of Dongting Lake from 2017 to 2022, this study aimed to clarify:…”
Section: Introductionmentioning
confidence: 99%